2015
DOI: 10.1186/s12879-015-1170-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of herpes zoster and associated events including stroke—a population-based cohort study

Abstract: BackgroundMore detailed understanding of herpes zoster (HZ) is called for in the context of an increasing observed frequency of disease, and ongoing discussions regarding potential consequences of the disease. Thus, population-based data on incidence and complications of HZ are needed.MethodsWe conducted a register-based cohort study in Västra Götaland County (population 1.5 million) in Sweden. We collected data on all patients diagnosed with HZ during the years 2008 to 2010 from population-based registers. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…More recently, a register-based cohort study in Sweden showed a 1.34-fold increased risk of stroke within 1 year after zoster in all age groups (7). As in the U.K. study, the risk of stroke in patients 39 years and younger was increased 10.3-fold within 1 year after zoster.…”
Section: Stroke After Zostermentioning
confidence: 78%
“…More recently, a register-based cohort study in Sweden showed a 1.34-fold increased risk of stroke within 1 year after zoster in all age groups (7). As in the U.K. study, the risk of stroke in patients 39 years and younger was increased 10.3-fold within 1 year after zoster.…”
Section: Stroke After Zostermentioning
confidence: 78%
“…A Swedish study indicates an elevated risk of stroke in the first year after herpes zoster, especially in younger patients (26). In these patients, arteritis is found with accompanying stenosis or occlusion as solitary or multiple lesions in large as well as small cerebral arteries.…”
Section: Complicating Diseasementioning
confidence: 99%
“…[29] Two cohort studies from Taiwan and Sweden observed a 1.3 fold increased risk of any (ischemic or hemorrhagic) stroke within 12 months after HZ. [3, 8] Another cohort study based on the Danish national registers in adults reported a 2.3-fold increased risk in the first two weeks, a 1.2-fold increased risk between two weeks and one year and a 1.1-fold increased risk after the first year following HZ as compared to the baseline period. [7] A similar temporal pattern was observed by Langan et al in a study based on the UK Clinical Practice Research Datalink (CPRD) database in adults: the risk of stroke was 1.6-fold increased in the first month, 1.4-fold increased between one and three months, 1.2-fold increased between four and six months and not increased between seven and twelve months after HZ.…”
Section: Introductionmentioning
confidence: 99%
“…after one year. [3, 5, 8] The Danish cohort study identified HZ patients based on acyclovir prescriptions which could give rise to misclassification of herpes simplex virus infection as HZ infections. [7] All six studies had the potential for residual confounding [2, 3, 5, 79] due to missing information on important risk factors of stroke.…”
Section: Introductionmentioning
confidence: 99%